Cardiac Stroke Prediction Framework using Hybrid Optimization Algorithm under DNN - Al-Shammari, N. K.; Alzamil, A. A.; Albadarn, M.; Ahmed, S. A.; Syed, M. B.; Alshammari, A. S.; Gabr, A. M. (Engineering, Technology & Applied Science Research, 2021)
Heart weakness and restricted blood flow into the cavities can cause a range of strokes from mild to severe Heart strokes are primary caused due to the fat deposited on artery walls. The process reduces the intake of blood and internally causes a pseudo vacuum of air bubbles leading to a stroke which can be identified with high-end instrumentations. In this article, a detailed evaluation is processed with a Hybrid Optimization Algorithm (HOA). In the proposed technique, data are preprocessed using a label encoder and the missing values of the dataset are filled. Whale Optimization Algorithm (WOA) and Crow Search Algorithm(CSA) extract inter-connected patterns and learning features using a dedicated Deep Neural Networking (DNN) support. The proposed Hybrid Optimization Algorithm extracts features and the resultant values demonstrate a high accuracy range of 97.34%.